Inglés técnico: Módulo intermedio - Tena Colunga, José Antonio (My University, 1995)
One interesting idea about communication is this: people us differente levels when they communicate. “Levels” are like the floors in a tall building. Communication takes place in different ways on each of the “floors”.
Keywords: gramática; tiempos; narrativas; verbales; adverbio